2015
DOI: 10.1016/j.matdes.2015.08.096
|View full text |Cite
|
Sign up to set email alerts
|

Influence of PCA on thermoelectric properties and hardness of nanostructured Ba–Cu–Si clathrates

Abstract: Nanostructuring has been considered an effective approach to enhance the thermoelectric (TE) performance of materials by reducing their lattice thermal conductivity. In the present study, we show the influence of a process control agent (PCA) for ball milling, Stearic acid (SA), on the nano-and microstructure and thermoelectric properties of type-I clathrates in the Ba-Cu-Si system, which are promising candidates for TE applications. The SA effectively reduces cold welding and prevents particle agglomeration d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The assembly of TEG devices is still particularly challenging, and consequently these devices have been applied only in niche applications [17]. With regard to TE materials, there is a problem of wide lattice thermal conductivity whereby nanostructuring has been considered as an effective approach to enhance the TE performance of materials by reducing their lattice thermal conductivity [18]. The introduction of large concentrations of lattice vacancies in silicon nano-films is noted for creating more than a 20-fold reduction in thermal conductivity, while Seebeck coefficient and electrical conductivity are largely maintained [19].…”
Section: Introductionmentioning
confidence: 99%
“…The assembly of TEG devices is still particularly challenging, and consequently these devices have been applied only in niche applications [17]. With regard to TE materials, there is a problem of wide lattice thermal conductivity whereby nanostructuring has been considered as an effective approach to enhance the TE performance of materials by reducing their lattice thermal conductivity [18]. The introduction of large concentrations of lattice vacancies in silicon nano-films is noted for creating more than a 20-fold reduction in thermal conductivity, while Seebeck coefficient and electrical conductivity are largely maintained [19].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the current research regarding thermoelectric refrigeration focuses on improving the ZT value of the materials while reducing their costs. Zolriasatein et al [94] showed that the grinding process of a material could influence its thermoelectric properties: as they added stearic acid during the grinding, the figure of merit of the material was enhanced by 15%. Hinterleitner et al [95] developed a new material, made from a thin layer of iron, vanadium, tungsten and aluminium applied to a silicon crystal, which ensures a ZT value between 5 and 6 at 300°C.…”
Section: Research Challengesmentioning
confidence: 99%
“…We used stearic acid, CH3(CH2)16CO2H, as a process control agent (PCA). The aim is to study how the PCA influences the behavior of grain size reduction during ball milling and growth during hot pressing . The process parameters for ball milling and hot pressing were fixed according to Sections and .…”
Section: Ball Milling and Hot Pressingmentioning
confidence: 99%